1999
DOI: 10.1046/j.1369-6513.1999.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to randomized clinical trials amongst out‐patients attending a medical oncology clinic

Abstract: Objective To assess the understanding of and attitudes towards randomized clinical trials amongst patients attending oncology outpatient clinics.Design Cross-sectional survey.Subjects Patients attending medical oncology out-patient clinics at a Sydney teaching hospital.Main outcome Patients' willingness to participate in a randomized clinical trial.Results Sixty consecutive patients were surveyed. The mean age was 55.2 (SD 14) years. Eighty-eight per cent of respondents thought that patients should be asked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 32 publications
4
58
0
2
Order By: Relevance
“…This differs somewhat from the recommendations of many authors, who have suggested communication workshops and specific training for physicians who must discuss recruitment into clinical trials with patients. [27][28][29] Unfortunately, the results of such communication workshops have not been consistent. 30 For the relatively large group of academic oncologists at the HRCC who are involved in clinical research, communication skills may be relatively homogeneous.…”
Section: Discussionmentioning
confidence: 98%
“…This differs somewhat from the recommendations of many authors, who have suggested communication workshops and specific training for physicians who must discuss recruitment into clinical trials with patients. [27][28][29] Unfortunately, the results of such communication workshops have not been consistent. 30 For the relatively large group of academic oncologists at the HRCC who are involved in clinical research, communication skills may be relatively homogeneous.…”
Section: Discussionmentioning
confidence: 98%
“…8 In an Australian study, 50% of clinicians surveyed were not participating in any trials, whereas a further 25% were participating in selected trials. 13 Various clinician barriers to recruitment have been identified, including lack of time and resources, patient characteristics that make some patients more difficult to approach than others, difficulties associated with obtaining informed consent and conveying complex information, and conflicts between the role of clinician and scientist. 8 Anxiety that disclosure of uncertainty may affect the physician-patient relationship also has been expressed.…”
mentioning
confidence: 99%
“…Une association identique entre rô le actif et participation a dé jà é té observé e [17]. Toutefois, d'autres auteurs n'ont pas mis en é vidence une telle relation [7] ou ont observé une relation opposé e [6]. Ici, les patientes ayant refusé de participer semblaient avoir un profil suffisamment autonome pour pouvoir refuser de participer si elles ne le souhaitaient pas (par aversion pour la randomisation par exemple).…”
Section: Discussionunclassified
“…Toutefois, certains pré -fè rent dé lé guer la responsabilité de ce choix à leur mé decin [16] comme pour les choix thé rapeutiques en gé né ral [4]. Les rares é tudes disponibles ont montré des ré sultats contradictoires concernant le lien entre la pré fé rence pour le mode de prise de dé cision et la participation à un ERC [6,7,11].…”
Section: Decision-making and Participation In Clinical Trialsunclassified